Assessing Metrics using LoRa Technology for Real-Time Landslide Monitoring within an IoT Framework - A, Inbavalli; R, Praveena; M, Kaviya (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
This research study introduces a groundbreaking approach to landslip monitoring through the seamless integration of low-power sensors with the versatile Arduino NANO platform, leveraging LoRa-based IoT technology. By facilitating real-time analysis of critical environmental variables such as water levels, soil movement, and humidity, this system enables early detection of soil instability, potentially preventing devastating landslides. Automated email notifications promptly alert authorities and communities to impending threats, enhancing crisis management effectiveness. LoRa technology's extensive coverage, affordability, and adaptability address shortcomings of traditional monitoring methods, while its versatility extends applicability beyond landslip monitoring. This proactive system empowers communities to intelligently respond to environmental changes, providing comprehensive, real-time monitoring for hazard identification and preventive action formulation, ultimately mitigating disaster risks and enhancing overall disaster response capabilities.